Students’ Perception on the Implementation of Teachers’ Verbal and Nonverbal Immediacy Behaviors on Enhancing Their English Learning Motivation - Nurdzizati, Ainun; Muhayyang, Maemuna; Amin, Fatimah Hidayahni; Tahir, Muhammad (Indonesian Journal of Educational Studies, 2025)
This study explores students’ perceptions of the implementation of teachers’ verbal and nonverbal immediacy behaviors in enhancing their English learning motivation. A quantitative research method was employed, with questionnaires used as the primary instrument for data collection. The study was conducted at SMAN 22 Makassar, involving 60 eleventh-grade students as respondents. The data obtained through the questionnaires were analyzed using descriptive statistical analysis. The findings revealed that students held generally positive perceptions toward both verbal and nonverbal immediacy behaviors demonstrated by their teachers. Among the most highly valued behaviors were showing concern, using humor, giving praise or positive feedback, smiling, standing with confidence, and employing expressive vocal tones. These results indicate that students are more motivated to engage in English learning when their teachers communicate in ways that foster emotional connection, attentiveness, and encouragement